Behavioral representations within the endogenous dual attentional pathways during audiovisual integration processing - Guan, Zhongtian; Yan, Mingli; He, Miao; Liu, Yubo; Zhang, Zhixi; Li, Chunlin (Frontiers in Neuroscience, 2025)
IntroductionAudiovisual integration processes are modulated by top-down attention and may involve different neural mechanisms under spatial, temporal, and neutral properties, which are externally manifested by subjects adopting different cognitive strategies. Composite behavioral indicators are able to assess the balance between speed and accuracy when subjects perform a task, thus further revealing behavioral representations of cognitive tasks. However, the cognitive strategies and neural mechanisms involved in audiovisual integration under endogenous attentional modulation are unclear, and in particular, the functional relationship between the dorsal and ventral pathways still needs to be thoroughly investigated.MethodsWe design only auditory (A), only visual (V), and audiovisual attention (VA) tasks based on the classical Posner paradigm with spatial, temporal and neutral cues for behavioral indicators, brain activation, and their correlations.ResultsOur results showed significant differences in behavioral performance between tasks, with weaker performance on the dual-channel task than on the single-channel task. The brain showed consistent activation in the frontal eye field, inferior parietal lobule, supplementary motor area, superior temporal gyrus, middle occipital gyrus and cuneus. The dorsal pathway is mainly associated with spatial processing and executive control, while the ventral pathway is involved in object recognition and semantic processing. In correlation analyses, proportions of correct responses (PC) showed a wider range of results. Spatio-temporal attention mobilized more cognitive resources than neutral attention in the audiovisual task and influenced execution strategies. Inverse efficiency score (IES) revealed endogenous attentional modulation of energy expenditure in the dual-channel task, whereas rate-correct score (RCS) revealed inter-task differences in correct response efficiency. Linear integrated speed–accuracy score (LISAS) and balanced integration score (BIS) showed different speed-accuracy balance in our task.ConclusionOur findings emphasize the synergy of functions and the dynamic synergy of cognitive processes in dorsal and ventral attentional pathways, which contribute to the management of cognitive flexibility and efficiency.